Electric bicycle rack for an urban environment : A bicycle rack that caters for the needs for electric bicycles in today’s society - Pålsson, Susanne (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2020)
More and more people commute to work, travel and use the electric bicycle as a daily means of transport. The need for bicycle racks, adapted for electric bicycles is growing and the demands on bicycle racks are higher than for bicycle racks for ordinary bicycles. This as they are very expensive to buy. On behalf of NOLA Industries, a bicycle rack for electric bicycles will be designed. The bicycle rack must also meet the need to recharge the batteries while the bicycle is parked and meet all found requirements from all stakeholders, which were collected during the project. The project is carried out by one student from Luleå University of Technology, who is studying M.Sc. in industrial design with a focus on product development. The project was carried out in Luleå with NOLA at a distance in Stockholm. The aim of the project was to come up with an idea for a bicycle rack that is suitable for public environments and that also fits into NOLA’s existing product range. At the beginning of the project, the time was planned using a Gantt scheme. The process used was CDIO consisting of four different phases. After the planning was completed, a benchmarking was made of how the situation looked and how the electric bicycles in today’s society work. The theory section was planned and introduced with a description of the line of technical design. The chapter was then followed up with relevant theory for the project. In order to find out what users think of existing bicycle racks and what were the desires for future bicycle racks, a survey was sent out. The work continued with several different information collection methods which were then followed up with creative work in the design phase. The final work included CAD models and renderings from keyshot of the finished concept. The final concept meets stakeholder requirements for an electric bike rack. It fulfill the need to be able to recharge the electric bike’s battery and to lock the electric bike in several points. The roof and the bicycle racks are equipped with led ...